Empirical Analysis of Distinct Entry Mode Strategies among Service Firms:: Case Studies from Australia - Shukla, Abhishek; Dow, Douglas; Misra, Roopali (Journal of Comparative International Management, 2012)
This paper investigates the aspect of market commitment by international service firms into the new host market. Australia was chosen as the host market because it is a strong service economy. This paper responds to several calls for studies focusing on service firm internationalization and the often neglected market commitment aspect. After splitting service firms into capital intensive and knowledge intensive categories, it is argued that they exhibit different patterns of initial resource commitment. Adopting a case study approach, the results indicate that capital intensive service firms enter a new host market with relatively lower resource commitment than knowledge intensive service firms and hence follow the Uppsala process model more closely.